UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN IPS MELALUI METODE PEMBELAJARAN PENEMUAN TERBIMBING PADA SISWA KELAS V.A SDN 26 PAINAN - Darma Yetni (STKIP Pesisir Selatan, 2018)
ABSTRACTBased on the learning outcomes of Class V.A SDN 26 Painan students in social studies subjects it was found that student learning outcomes in social studies subjects were still very low. The average student learning outcomes are still under the KKM. The purpose of this study was to describe and obtain information about efforts to improve student learning outcomes in social studies subjects through the Guided Discovery Learning Method in Class V.A SDN 26 Painan South Coastal District. This research is a classroom action research. The procedure of research in this study includes planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 33 students of Class V.A SDN 26 Painan. Research data was collected using observation sheets and daily tests. Data were analyzed using percentages. Based on the results of research and discussion that have been put forward, it can be concluded that the Guided Discovery Learning Method can improve student learning outcomes in social studies subjects at SDN 26 Painan. Student learning outcomes from cycle I to cycle II. Student learning outcomes in the first cycle were 51.97 (Enough) increased to 83.67 (Good) with an increase of 31.70%.